My English therapist self lost in translation with an Italian client - Santin, Chiara (Murmurations: Journal of Transformative Systemic Practice, 2018)
This short story reflects some of the richness and complexity of working and thinking across languages and cultures i.e. Italian and English, a UK-trained professional self and Italian personal self and the complex interplay of these in therapy. It is a story about me from when I was a newly qualified systemic and family psychotherapist, sharing my inner conversation, dilemmas, hidden emotions and sense of incompetence and confusion about using my first language in therapy in the UK with a male Italian client, muddling through unclear professional boundaries. The story highlights the importance of self-reflexivity and transparency with our own cultural and gendered assumptions in order to promote personal and professional development. A male Mexican non-therapist designer complements the original script with some illustrations. This interplay between art and therapy becomes an enriching dialogue across professional boundaries, which is embedded in the final story. It results in an interweaving of multiple stories and provides a bridge between different perspectives e.g. art and therapy, male and female, therapy and non-therapy, within and outside own culture and language. Finally, the story is presented within a systemic framework and key systemic ideas about living in multiple languages, the socio-constructionist nature of meanings and emotions, the emotional posture in therapy when faced with many dilemmas about ethics, competence, professional boundaries, differences and similarities and their complex interplay in a therapeutic encounter. Abstract (Italian) Questa breve storia riflette la ricchezza e complessità quando si lavora e si pensa in lingue e culture diverse, in questo caso la lingua Italiana e Inglese, il self professionale formato in UK in lingua Inglese e il self personale radicato nella lingua e cultura Italiana e come interagiscono in terapia. È una storia di una psicoterapeuta sistemica all'inizio della carriera professionale che condivide pensieri, dilemmi, emozioni nascoste e un senso di incompetenza e confusione usando la lingua madre in terapia in UK con un cliente italiano, muovendosi a tentoni attraverso labili confini professionali. La storia mette in rilievo l'importanza della riflessione su di s'e la trasparenza con i propri pre-concetti derivanti dalla propria cultura e genere diversi per promuovere la crescita personale e professionale. Un designer Messicano, al di fuori del mondo della psicoterapia, completa lo scritto originale con alcune illustrazioni e questo connubio tra arte e psicoterapia diventa un ricco dialogo che viene incorporato nella storia finale. Il risultato è un intreccio di storie multiple che offrono un ponte tra diverse prospettive; per esempio arte e psicoterapia, genere maschile e femminile, terapia e non-terapia, all'interno e al di fuori della propria cultura di origine e linguaggio. La storia è presentata usando un orientamento teorico sistemico specificatamente sul vivere usando vari linguaggi, la natura socio-construttiva dei significati e le emozioni, la postura terapeutica quando a confronto con molti dilemmi sull'etica, i confini professionali, la propria competenza, similarità e differenze e la complessità del loro manifestarsi in un incontro terapeutico.